New challenges for Singapore telecom - Azleen Annuar AIi (2013)
Telecommunications is acquiring strategic importance for economic growth and development As economic activity expands to a global scale, its dependence on the flow of information also increases This is also evident from the tremendous growth in the telecommunications industry. In l995, the global market generated US$74l billion A further growth of7-8 per cent is expected for 1996.